Main methods to detect multiple sclerosis (MS) lesions in patients with MSatients with MS - Hasyma Abu Hassan, Abdullah Dhaifallah Almutairi Rozi Mahmud, Subapriya Suppiah, (Opción, 2019)
The aim of the study is to investigate the main methods to detect Multiple Sclerosis (MS) Lesions in patients with MS. This study was a systematic review to detect main methods to detect of MS lesion in patients with MS. As a result, we found that MRI is the most accuracy and powerful tool for diagnosing a MS especially in early phase. In conclusion, the McDonald criteria is the best criteria that it has been proposed and revised in recently years to diagnose of MS based on clinical presentation and MRI.